High-capacity sodium ion battery layered positive electrode material and preparation method and application thereof
By adopting the collaborative doping technology of Al and Sb in the sodium ion battery positive electrode material, the problems of cyclic stability and low efficiency of the existing sodium ion battery positive electrode material are solved, and a high capacity, stability and high efficiency of sodium ion battery positive electrode material is achieved.
Patent Information
- Application Number
- CN202411662642.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-20
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-11-20
AI Technical Summary
The existing sodium ion battery positive electrode materials have problems such as capacity attenuation, unsatisfactory cycle stability and low Coulomb efficiency during the cycle.
The layered cathode material of high-capacity sodium ion battery was prepared by direct solid-phase calcination. Through the coordinated doping of Al and Sb, the active elements Fe and inactive elements Mn were replaced, and the lattice structure was stabilized, and the reversible capacity and cyclic stability were improved.
The adverse phase change of the positive electrode material of sodium ion battery in electrochemical reaction is significantly suppressed, the reversible capacity and cycle stability of sodium ion battery are improved, and the first-circuit Coulomb efficiency and capacity retention rate are optimized.
Smart Images

Figure CN119191387B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of sodium ion batteries, and in particular relates to a high-capacity sodium ion battery layered positive electrode material and a preparation method and application thereof. Background Art
[0002] Lithium-ion batteries have the advantages of high energy density, high power density, high operating voltage and good cycle performance, and are widely used in portable electronic devices. However, the reserves of lithium resources in the earth's crust are very small, and there is a problem of uneven distribution in the region, which leads to rising costs year by year, limiting its application in the field of large-scale power storage. Sodium-ion batteries have a similar charging and discharging mechanism to lithium-ion batteries, and sodium ions and lithium ions have very similar physical and chemical properties. The most important thing is that sodium resources are very abundant and widely distributed, so the development of sodium-ion battery technology has a positive significance for large-scale power storage systems. While reducing costs, sodium-ion batteries also have high specific energy density, excellent energy conversion efficiency and long charge and discharge cycle life, which provides an opportunity to gradually replace the use of lead-acid batteries. As a critical functional component of sodium-ion batteries, positive electrode materials have an important influence on the performance of sodium-ion batteries. Among the current mainstream positive electrode materials, layered transition metal oxides are considered to be one of the most promising positive electrode materials for sodium-ion batteries due to their high average voltage, high specific capacity and easy synthesis. Layered transition metal oxides are divided into P2, O3 and other crystal forms. Compared with P2 materials, O3 materials have the advantage of high capacity. O3-type nickel-manganese-iron-based layered oxides have attracted widespread attention due to their high capacity. However, during the cycle, due to the deintercalation of sodium and the valence change of active elements such as Ni and Fe, the lattice distortion, lattice oxygen evolution, and element mixing of the sodium layer or transition metal layer are caused, resulting in unsatisfactory cycle stability. In addition, the current sodium-ion battery positive electrode materials still have the problem of low first coulomb efficiency. Summary of the invention
[0003] In view of the shortcomings of the prior art, the object of the present invention is to provide a method for preparing a high-capacity sodium ion battery layered positive electrode material, wherein the preparation method adopts a direct solid phase calcination method.
[0004] Another object of the present invention is to provide a high-capacity sodium ion battery layered positive electrode material obtained by the above preparation method.
[0005] Another object of the present invention is to provide an application of the above-mentioned high-capacity sodium ion battery layered positive electrode material in a sodium ion battery, and to prepare a sodium ion battery using the high-capacity sodium ion battery layered positive electrode material of the present invention, thereby inhibiting the capacity decay of the sodium ion battery and improving the cycle stability and the first-cycle coulombic efficiency.
[0006] The purpose of the present invention is achieved through the following technical solutions.
[0007] A method for preparing a high-capacity sodium ion battery layered positive electrode material comprises the following steps:
[0008] S1, mixing a sodium source, a nickel source, an iron source, a manganese source, an aluminum source and an antimony source until uniform, to obtain a precursor powder, wherein, by amount of substance, the ratio of sodium in the sodium source, nickel in the nickel source, iron in the iron source, manganese in the manganese source, aluminum in the aluminum source and antimony in the antimony source is (0.88-1): 0.35: 0.2: 0.4: 0.025: 0.025;
[0009] In S1, the sodium source is one or a mixture of sodium carbonate, sodium bicarbonate, sodium nitrate, sodium acetate, sodium oxalate and sodium citrate.
[0010] In S1, the nickel source is one or a mixture of nickel oxide, nickel chloride, nickel nitrate, nickel sulfate, nickel carbonate, nickel acetate, nickel oxalate and nickel citrate.
[0011] In S1, the iron source is one or a mixture of iron oxide, iron chloride, iron nitrate, iron sulfate, iron carbonate, iron acetate, iron oxalate and iron citrate.
[0012] In S1, the manganese source is one or a mixture of manganese oxide, manganese chloride, manganese nitrate, manganese sulfate, manganese carbonate, manganese acetate, manganese oxalate and manganese citrate.
[0013] In S1, the aluminum source is one or a mixture of aluminum oxide, aluminum chloride, aluminum nitrate, aluminum sulfate, aluminum carbonate, aluminum acetate, aluminum oxalate and aluminum citrate.
[0014] In S1, the antimony source is one or a mixture of antimony oxide, antimony chloride, antimony nitrate, antimony sulfate, antimony carbonate, antimony acetate, antimony oxalate and antimony citrate.
[0015] In S1, the method of mixing the sodium source, nickel source, iron source, manganese source, aluminum source and antimony source until they are uniform is one of a dry mixing method, a spray drying method, a sol-gel method and a co-precipitation method.
[0016] In the above technical solution, the dry mixing method is: mixing the sodium source, nickel source, iron source, manganese source, aluminum source and antimony source, and ball milling at a speed of 1000-1400 rpm for 1-2 hours until uniform, to obtain a precursor powder.
[0017] S2, sintering the precursor powder at 600-1200° C. for 6-24 h to obtain a high-capacity sodium ion battery layered positive electrode material, and the sodium ion battery prepared from the high-capacity sodium ion battery layered positive electrode material has a first-cycle discharge capacity of 164 mAh g at a current density of 1C. -1 , the capacity retention rate is as high as 82%.
[0018] In S2, the rate of heating to 600~1200℃ is 3~5℃ / min.
[0019] The high-capacity sodium ion battery layered positive electrode material obtained by the above preparation method.
[0020] Application of the above-mentioned high-capacity sodium-ion battery layered positive electrode material in sodium-ion batteries.
[0021] In the above technical solution, the sodium ion battery has a first cycle discharge capacity of 164 mAhg at a current density of 1C. -1 The discharge capacity after 100 cycles is 134.5 mAh g -1 , the capacity retention rate is 82%.
[0022] In the above technical solution, the sodium ion battery includes a liquid sodium ion battery and a solid sodium ion battery.
[0023] Compared with the prior art, the present invention has the following beneficial effects:
[0024] The present invention adopts Al and Sb synergistic doping to replace the active elements and inactive elements in the layered positive electrode material of the high-capacity sodium ion battery, wherein Al doping replaces the active element Fe, and Sb doping replaces the inactive element Mn, which effectively inhibits the adverse phase change of the layered positive electrode material of the high-capacity sodium ion battery in the electrochemical reaction, improves the reversible capacity of the sodium ion battery, and optimizes the cycle stability and the first-cycle coulomb efficiency of the sodium ion battery. The obtained sodium ion battery has a high first-cycle coulomb efficiency (optimum is 94%) and excellent cycle stability (after 100 cycles, the capacity retention rate is optimally 82%). BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 XRD diagram of the high-capacity sodium ion battery layered positive electrode material prepared in Examples 1 to 5;
[0026] Figure 2 The charge and discharge curves of the sodium ion batteries prepared in Examples 6 to 10 are as follows: Figure 2 a~ Figure 2 e are the charge and discharge curves of the sodium ion batteries prepared in Examples 6 to 10 respectively;
[0027] Figure 3The cycle performance diagram of the sodium ion battery prepared in Examples 6 to 10 at a current density of 1C;
[0028] Figure 4 This is a cycle performance diagram of the sodium ion battery prepared in Example 6 at a current density of 0.5C;
[0029] Figure 5 This is a cycle performance diagram of the sodium ion battery prepared in Example 6 at a current density of 2C;
[0030] Figure 6 XRD diagram of the sodium ion battery positive electrode material prepared in Comparative Examples 1 to 3;
[0031] Figure 7 The charge and discharge curves of the sodium ion batteries prepared in Comparative Examples 4 to 6 are as follows: Figure 7 a~ Figure 7 c are the charge and discharge curves of the sodium ion batteries prepared in Comparative Examples 4 to 6 respectively;
[0032] Figure 8 The cycle performance diagram of the sodium ion battery prepared in Comparative Examples 4 to 6 at a current density of 1C;
[0033] Fig. 9 This is an EDS image of the high-capacity sodium-ion battery layered positive electrode material prepared in Example 1;
[0034] Fig.10 This is the EDS image of the sodium ion battery positive electrode material prepared in Comparative Example 1;
[0035] Fig.11 This is the EDS image of the sodium ion battery positive electrode material prepared in Comparative Example 2;
[0036] Fig.12 This is the EDS image of the sodium ion battery positive electrode material prepared in Comparative Example 3. DETAILED DESCRIPTION
[0037] The technical solution of the present invention is further described below in conjunction with specific embodiments.
[0038] The raw material information involved in the following examples is as follows:
[0039] Sodium carbonate, 99.9%, Shanghai McLean Biochemical Technology Co., Ltd.; nickel oxide (NiO), analytical grade, Shanghai Aladdin Biochemical Technology Co., Ltd.; ferric oxide (Fe2O3), analytical grade, Shanghai McLean Biochemical Technology Co., Ltd.; manganese carbonate (MnCO3), AR, Shanghai McLean Biochemical Technology Co., Ltd.; aluminum oxide (Al2O3), AR, Shanghai McLean Biochemical Technology Co., Ltd.; antimony pentoxide (Sb2O5), 99.9%, Shanghai McLean Biochemical Technology Co., Ltd. Positive electrode shell: CR2032, Taizhou Yajun Battery Material Co., Ltd.; gasket: Φ15.8*1.0mm, Dongguan Kelude Experimental Equipment Technology Co., Ltd.; shrapnel: 15.4*1.1mm (funnel-shaped), Dongguan Kelude Experimental Equipment Technology Co., Ltd.; negative electrode shell: CR2032, Taizhou Yajun Battery Material Co., Ltd.
[0040] The instrument information involved in the following examples is as follows:
[0041] The XRD patterns were measured by an X-ray diffractometer (ARL EQUINOX 3000, Thermo Fisher Scientific) at 40 kV and 40 mA in the 2θ range of 10 to 80°.
[0042] On the LAND system (LAND CT2001A, China), 2.0 - 4.2 V (vs. Na / Na + ) potential window, constant current charge and discharge measurements and rate performance tests were performed on the following sodium ion batteries.
[0043] Scanning electron microscopy (SEM, Quanta FEG, USA) was used to observe the microstructure, surface morphology and element distribution (EDS).
[0044] The present invention suppresses the adverse phase change of high-capacity sodium ion battery layered positive electrode materials in electrochemical reactions through the synergistic doping of Al and Sb, so that the sodium ion battery has high reversible capacity and cycle stability. The high-capacity sodium ion battery layered positive electrode material of the present invention is based on Ni, Fe and Mn as the basic framework, wherein Ni and Fe are active elements that contribute to capacity through their valence changes, while Mn is an inactive element that is mainly used to stabilize the phase lattice structure. The present invention uses Al and Sb elements for co-doping, Al doping replaces the active element Fe, and Sb doping replaces the inactive element Mn. Through the synergistic effect of the two, the lattice is stabilized and the reversible capacity is improved, thereby optimizing the cycle stability and first-cycle coulomb efficiency of the sodium ion battery.
[0045] Embodiment 1~5
[0046] A method for preparing a high-capacity sodium ion battery layered positive electrode material comprises the following steps:
[0047] S1, Na source, Ni source, Fe source, Mn source, Al source and Sb source are mixed, and ball milled at a speed of 1400 rpm for 2 hours until uniform (dry mixing method) to obtain a precursor powder, wherein, by amount of substance, the ratio of Na in Na source, Ni in Ni source, Fe in Fe source, Mn in Mn source, Al in Al source and Sb in Sb source is X, and the value of X is shown in Table 1, the Na source is sodium carbonate, the Ni source is Ni oxide (NiO), the Fe source is Fe oxide (Fe2O3), the Mn source is Mn carbonate (MnCO3), the Al source is Al oxide (Al2O3), and the Sb source is Sb oxide (Sb2O5);
[0048] S2, placing the precursor powder in a muffle furnace, heating it to 900°C at a rate of 5°C / min in an air atmosphere and sintering it at 900°C for 12 h to obtain a high-capacity sodium ion battery layered positive electrode material.
[0049] Table 1
[0050]
[0051] Comparative Example 1
[0052] A sodium ion battery positive electrode material (Na 0.88 Ni 0.35 Fe 0.225 Mn 0.425 O2) preparation method, comprising the following steps:
[0053] S1, mixing a Na source, a Ni source, a Fe source and a Mn source, and ball milling at a speed of 1400 rpm for 2 hours until uniform, to obtain a first substance, wherein, in terms of the amount of the substances, the ratio of Na in the Na source, Ni in the Ni source, Fe in the Fe source and Mn in the Mn source is 0.924:0.35:0.225:0.425. The Na source is sodium carbonate, the Ni source is Ni oxide (NiO), the Fe source is Fe oxide (Fe2O3), and the Mn source is Mn carbonate (MnCO3);
[0054] S2, placing the first substance in a muffle furnace, raising the temperature to 900°C at a rate of 5°C / min in an air atmosphere, and sintering at 900°C for 12 h to obtain a positive electrode material for a sodium ion battery.
[0055] Comparative Example 2
[0056] A sodium ion battery positive electrode material (Na 0.88 Ni 0.35 Fe 0.225 Mn 0.4 Sb 0.025O2) preparation method, comprising the following steps:
[0057] S1, mixing a Na source, a Ni source, a Fe source, a Mn source and a Sb source, and ball milling at a speed of 1400 rpm for 2 hours until uniform, to obtain a second substance, wherein, by amount of substance, the ratio of Na in the Na source, Ni in the Ni source, Fe in the Fe source, Mn in the Mn source and Sb in the Sb source is 0.924:0.35:0.225:0.4:0.025, the Na source is sodium carbonate, the Ni source is Ni oxide (NiO), the Fe source is Fe oxide (Fe2O3), the Mn source is Mn carbonate (MnCO3), and the Sb source is Sb oxide (Sb2O5);
[0058] S2, placing the second substance in a muffle furnace, raising the temperature to 900°C at a rate of 5°C / min in an air atmosphere and sintering at 900°C for 12 h to obtain a positive electrode material for a sodium ion battery.
[0059] Comparative Example 3
[0060] A sodium ion battery positive electrode material (Na 0.88 Ni 0.35 Fe 0.2 Mn 0.425 Al 0.025 O2) preparation method, comprising the following steps:
[0061] S1, mixing a Na source, a Ni source, a Fe source, a Mn source and an Al source, and ball milling at a rotation speed of 1400 rpm for 2 hours until uniform, to obtain a third substance, wherein, by amount of substance, the ratio of Na in the Na source, Ni in the Ni source, Fe in the Fe source, Mn in the Mn source and Al in the Al source is 0.924:0.35:0.2:0.425:0.025, the Na source is sodium carbonate, the Ni source is Ni oxide (NiO), the Fe source is Fe oxide (Fe2O3), the Mn source is Mn carbonate (MnCO3), and the Al source is Al oxide (Al2O3);
[0062] S2, placing the third substance in a muffle furnace, raising the temperature to 900°C at a rate of 5°C / min in an air atmosphere and sintering at 900°C for 12 h to obtain a positive electrode material for a sodium ion battery.
[0063] Examples 6 to 10 and Comparative Examples 4 to 6
[0064] A sodium ion battery comprises: a positive electrode sheet, a separator, a negative electrode sheet and an electrolyte. In a glove box, the positive electrode shell, the positive electrode sheet, the separator, the negative electrode sheet, the gasket, the spring sheet and the negative electrode shell are assembled in order to obtain a sodium ion battery, wherein the electrolyte in the electrolyte is NaClO4, the concentration of the electrolyte in the electrolyte is 1M, the solvent is a mixture of propylene carbonate (PC) and fluoroethylene carbonate (FEC), and the ratio of propylene carbonate (PC) to fluoroethylene carbonate (FEC) is 95:5 by volume, the negative electrode sheet is a sodium sheet, and the separator is a glass fiber separator (GF / D whatman). The method for obtaining the positive electrode sheet is: mixing a positive electrode material, acetylene black and a polyvinylidene fluoride (PVDF) solution (the polyvinylidene fluoride solution is a mixture of polyvinylidene fluoride and N-methylpyrrolidone, and the concentration of PVDF in the polyvinylidene fluoride solution is 20 mg mL -1 ) and grind them to be uniform to obtain slurry. The slurry is evenly coated on the aluminum foil as the current collector with a scraper and dried in a vacuum oven at 80°C. After drying, it is cut into small discs with a diameter of 12 mm as the positive electrode sheets (the loading amount of the slurry on the small discs with a diameter of 12 mm is 2 mg cm -2 ). The ratio of the positive electrode material, acetylene black and polyvinylidene fluoride (PVDF) in the solution is 7:2:1 by mass. The positive electrode material is one of the high-capacity sodium ion battery layered positive electrode materials prepared in Examples 1 to 5 and the sodium ion battery positive electrode materials prepared in Comparative Examples 1 to 3 (as shown in Table 2).
[0065] Table 2
[0066]
[0067] The XRD patterns of the high-capacity sodium ion battery layered cathode materials prepared in Examples 1 to 5 are as follows: Figure 1 As shown in the figure, the XRD spectrum shows characteristic diffraction peaks at 2θ = 16.6°, 35.5°, 41.9° and 62.9°, which can be compared with the layered hexagonal structure of NaNi 0.5 Mn 0.5 The (003), (101), (104) and (110) peaks of O2 correspond to each other (R3′m, PDF 54-0887). XRD analysis proves that the high-capacity sodium ion battery layered cathode materials prepared in Examples 1 to 5 are O3 phase.
[0068] The charge and discharge curve of the sodium ion battery prepared in Example 6 at 0.2C is as follows Figure 2 As shown in a, the charge and discharge curve of the sodium ion battery prepared in Example 7 at 0.2C is as shown in Figure 2 As shown in b, the charge and discharge curve of the sodium ion battery prepared in Example 8 at 0.2C is as follows Figure 2As shown in c, the charge and discharge curve of the sodium ion battery prepared in Example 9 at 0.2C is as follows Figure 2 As shown in d, the charge and discharge curve of the sodium ion battery prepared in Example 10 at 0.2C is as follows Figure 2 At 2-4.2V and 0.2C, the first cycle charge capacity of the sodium ion battery prepared in Example 6 is 201.3 mAh g -1 , the discharge capacity is 189.2 mAh g -1 The first cycle coulombic efficiency is 94%; the first cycle charging capacity of the sodium ion battery prepared in Example 7 is 205.8 mAh g -1 , the discharge capacity is 171 mAh g -1 The first cycle coulombic efficiency is 83%; the first cycle charging capacity of the sodium ion battery prepared in Example 8 is 209.8 mAh g -1 , the discharge capacity is 178 mAh g -1 The first cycle coulombic efficiency is 84.8%; the first cycle charging capacity of the sodium ion battery prepared in Example 9 is 208 mAh g -1 , the discharge capacity is 178.8 mAh g -1 The first cycle coulombic efficiency is 86%; the first cycle charging capacity of the sodium ion battery prepared in Example 10 is 205 mAh g -1 , the discharge capacity is 174.4 mAh g -1 , the first-cycle Coulomb efficiency is 85%.
[0069] At 2-4.2 V and 0.5 C current density, the first cycle charge capacity of the sodium ion battery prepared in Example 6 was 182.6 mAh g -1 , the discharge capacity is 172 mAh g -1 The first cycle coulombic efficiency is 94.2%; the first cycle charging capacity of the sodium ion battery prepared in Example 7 is 191.7 mAh g -1 , the discharge capacity is 170 mAh g -1 The first cycle coulombic efficiency is 88.7%; the first cycle charging capacity of the sodium ion battery prepared in Example 8 is 180.3 mAh g -1 , the discharge capacity is 168 mAh g -1 The first cycle coulombic efficiency is 93.2%; the first cycle charging capacity of the sodium ion battery prepared in Example 9 is 192.8 mAh g -1 , the discharge capacity is 175.5 mAh g -1 The first cycle coulombic efficiency is 91%; the first cycle charging capacity of the sodium ion battery prepared in Example 10 is 190.8 mAh g -1, the discharge capacity is 169.8 mAh g -1 , the first-cycle Coulomb efficiency is 89%.
[0070] The cycle performance of the sodium ion battery prepared in Examples 6 to 10 at 2-4.2V and 1C for 100 cycles is shown in the figure below. Figure 3 As shown, the first cycle discharge capacity of the sodium ion battery prepared in Example 6 is 164 mAh g -1 The discharge capacity after 100 cycles is 134.5 mAh g -1 The capacity retention rate is 82%; the first cycle discharge capacity of the sodium ion battery prepared in Example 7 is 149 mAh g -1 The discharge capacity after 100 cycles is 116 mAh g -1 The capacity retention rate is 77.8%; the first cycle discharge capacity of the sodium ion battery prepared in Example 8 is 161.7 mAh g -1 The discharge capacity after 100 cycles is 126 mAh g -1 The capacity retention rate is 77.9%. The first cycle discharge capacity of the sodium ion battery prepared in Example 9 is 164 mAh g -1 The discharge capacity after 100 cycles is 127.5 mAh g -1 The capacity retention rate is 77.7%; the first cycle discharge capacity of the sodium ion battery prepared in Example 10 is 156 mAh g -1 The discharge capacity after 100 cycles is 118 mAh g -1 , the capacity retention rate is 75.6%.
[0071] The cycle performance of the sodium ion battery prepared in Example 6 at 2-4.2V, 0.5C for 100 cycles is shown in the figure below: Figure 4 As shown, the first cycle discharge capacity of the sodium ion battery prepared in Example 6 is 172 mAh g -1 The discharge capacity after 100 cycles is 137.4 mAh g -1 , the capacity retention rate is 79.8%.
[0072] The cycle performance of the sodium ion battery prepared in Example 6 at 2-4.2V, 2C for 200 cycles is shown in the figure below: Figure 5 As shown, the first cycle discharge capacity of the sodium ion battery prepared in Example 6 is 150 mAh g -1 The discharge capacity after 200 cycles is 117 mAh g -1 , the capacity retention rate is 78%.
[0073] The XRD patterns of the sodium ion battery positive electrode materials prepared in Comparative Examples 1 to 3 are as follows: Figure 6As shown in the figure, the XRD spectrum shows characteristic diffraction peaks at 2θ = 16.6°, 35.5°, 41.9° and 62.9°, which can be compared with the layered hexagonal structure of NaNi 0.5 Mn 0.5 The (003), (101), (104) and (110) peaks of O2 correspond to each other (R3′m, PDF 54-0887). XRD analysis shows that the positive electrode materials for sodium ion batteries prepared in Comparative Examples 1 to 3 are in the O3 phase.
[0074] The charge and discharge curve of the sodium ion battery prepared in Comparative Example 4 at 0.2C is as follows Figure 7 As shown in a, the charge and discharge curve of the sodium ion battery prepared in Comparative Example 5 at 0.2C is as shown in Figure 7 As shown in b, the charge and discharge curve of the sodium ion battery prepared in Comparative Example 6 at 0.2C is as follows Figure 7 As shown in c, at 2-4.2V and 0.2C, the first cycle charging capacity of the sodium ion battery prepared in Comparative Example 4 is 212.7 mAh g -1 , the discharge capacity is 177 mAh g -1 The first cycle coulombic efficiency is 83.2%; the first cycle charging capacity of the sodium ion battery prepared in comparative example 5 is 209 mAh g -1 , the discharge capacity is 170 mAh g -1 The first cycle coulombic efficiency is 81.3%; the first cycle charging capacity of the sodium ion battery prepared in comparative example 6 is 210.2 mAh g -1 , the discharge capacity is 176 mAh g -1 , the first-cycle Coulomb efficiency is 83.7%.
[0075] At 2-4.2V and 0.5C current density, the first cycle charging capacity of the sodium ion battery prepared in Comparative Example 4 was 202.5 mAh g -1 , the discharge capacity is 164 mAh g -1 The first cycle coulombic efficiency is 81%; the first cycle charging capacity of the sodium ion battery prepared in comparative example 5 is 203.8 mAh g -1 , the discharge capacity is 162 mAh g -1 The first cycle coulombic efficiency is 79.5%; the first cycle charging capacity of the sodium ion battery prepared in comparative example 6 is 195.5 mAh g -1 , the discharge capacity is 160.5 mAhg -1 , the first-cycle Coulomb efficiency is 82.1%.
[0076] The cycle performance of the sodium ion battery prepared in Comparative Examples 4 to 6 at 2-4.2V and 1C for 100 cycles is shown in the figure below: Figure 8As shown in the figure, the first cycle discharge capacity of the sodium ion battery prepared in Comparative Example 4 is 164.3 mAh g -1 The discharge capacity after 100 cycles is 124.8 mAh g -1 The capacity retention rate is 75.9%; the first cycle discharge capacity of the sodium ion battery prepared in Comparative Example 5 is 153.5 mAh g -1 The discharge capacity after 100 cycles is 117.7 mAh g -1 The capacity retention rate is 76.6%; the first cycle discharge capacity of the sodium ion battery prepared in Comparative Example 6 is 154.8 mAh g -1 The discharge capacity after 100 cycles is 113.7 mAh g -1 , the capacity retention rate is 73.4%.
[0077] Example 1 The element distribution diagram (EDS) of the obtained high-capacity sodium ion battery layered positive electrode material is as follows Fig. 9 As shown, the EDS spectrum shows that the material prepared in Example 1 contains Na, Ni, Fe, Mn, Al, Sb, and O elements, and each element is evenly distributed in the material.
[0078] The element distribution diagram (EDS) of the high-capacity sodium ion battery layered positive electrode material prepared in Comparative Example 1 is as follows Fig.10 As shown, the EDS spectrum shows that the material prepared in Comparative Example 1 contains Na, Ni, Fe, Mn, and O elements, and each element is evenly distributed in the material.
[0079] The element distribution diagram (EDS) of the high-capacity sodium ion battery layered positive electrode material prepared in Comparative Example 2 is as follows Fig.11 As shown, the EDS spectrum shows that the material prepared in Comparative Example 2 contains Na, Ni, Fe, Mn, Sb, and O elements, and each element is evenly distributed in the material.
[0080] The element distribution diagram (EDS) of the high-capacity sodium ion battery layered positive electrode material prepared in Comparative Example 3 is as follows Fig.12 As shown, the EDS spectrum shows that the material prepared in Comparative Example 3 contains Na, Ni, Fe, Mn, Al, and O elements, and each element is evenly distributed in the material.
[0081] In summary, in the electrochemical test, the first-cycle coulombic efficiency and cycle stability of the sodium ion battery prepared in Example 1 are higher than those of the comparative example, proving that the synergistic effect of co-doping Al and Sb elements in a suitable proportion enables the first-cycle coulombic efficiency and cycle stability of the sodium ion battery to be simultaneously improved.
[0082] The first cycle discharge specific capacity, the discharge specific capacity after 100 cycles and the capacity retention rate of the sodium ion batteries of Examples 6 to 10 and Comparative Examples 4 to 6 at a current density of 1C are shown in Table 3.
[0083] Table 3
[0084]
[0085] The first cycle discharge specific capacity, the discharge specific capacity after 100 cycles and the capacity retention rate of the sodium ion batteries of Examples 6 to 10 and Comparative Examples 4 to 6 at a current density of 0.5C are shown in Table 4.
[0086] Table 4
[0087]
[0088] The first cycle discharge specific capacity, the discharge specific capacity after 200 cycles and the capacity retention rate of the sodium ion batteries of Examples 6 to 10 and Comparative Examples 4 to 6 at a current density of 2C are shown in Table 5.
[0089] Table 5
[0090]
[0091] The present invention is described above by way of example. It should be noted that, without departing from the core of the present invention, any simple deformation, modification or other equivalent replacement that can be made by those skilled in the art without inventive effort falls within the protection scope of the present invention.
Claims
1. A method for preparing a high-capacity sodium ion battery layered positive electrode material, characterized in that: The following steps are involved: S1, mixing a sodium source, a nickel source, an iron source, a manganese source, an aluminum source and an antimony source until uniform, to obtain a precursor powder, wherein, by amount of substance, the ratio of sodium in the sodium source, nickel in the nickel source, iron in the iron source, manganese in the manganese source, aluminum in the aluminum source and antimony in the antimony source is 0.924:0.35:0.2:0.4:0.025:0.025; S2, sintering the precursor powder at 600-1200°C for 6-24 h to obtain a high-capacity sodium ion battery layered positive electrode material, co-doping aluminum and antimony elements, aluminum doping replaces the active element iron, and antimony doping replaces the inactive element manganese. The sodium ion battery prepared by the high-capacity sodium ion battery layered positive electrode material has a first cycle charge capacity of 201.3 mAh g at a current density of 0.2C. -1 , the discharge capacity is 189.2 mAh g -1 The first cycle coulombic efficiency is 94%, and the first cycle discharge capacity is 164 mAh g at 1C current density. -1 .
2. The preparation method according to claim 1, characterized in that: In S1, the method of mixing the sodium source, nickel source, iron source, manganese source, aluminum source and antimony source until they are uniform is one of a dry mixing method, a spray drying method, a sol-gel method and a co-precipitation method.
3. The preparation method according to claim 2, characterized in that: The dry mixing method comprises: mixing a sodium source, a nickel source, an iron source, a manganese source, an aluminum source and an antimony source, and ball milling the mixture at a rotation speed of 1000-1400 rpm for 1-2 hours until the mixture is uniform, thereby obtaining a precursor powder.
4. The preparation method according to claim 1, characterized in that: In S2, the rate of heating to 600~1200℃ is 3~5℃ / min.
5. The preparation method according to claim 1, characterized in that: At 1C current density, the discharge capacity of the sodium-ion battery after 100 cycles is 134.5 mAh g -1 .
Citation Information
Patent Citations
Doped layered positive electrode material, synthesis method and application in sodium ion battery
CN116598471A
Layered oxide positive electrode material for sodium ion battery, preparation method and application
CN118315580A